2014
DOI: 10.1016/j.yjmcc.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic screen quantifying differential regulation of cardiac myocyte hypertrophy identifies CITED4 regulation of myocyte elongation

Abstract: Cardiac hypertrophy is controlled by a highly connected signaling network with many effectors of cardiac myocyte size. Quantification of the contribution of individual pathways to specific changes in shape and transcript abundance is needed to better understand hypertrophy signaling and to improve heart failure therapies. We stimulated cardiac myocytes with 15 hypertrophic agonists and quantitatively characterized differential regulation of 5 shape features using high-throughput microscopy and transcript level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 63 publications
0
45
0
Order By: Relevance
“…Computational models can help identify the mechanisms by which these drugs suppress fibrosis and can identify therapeutic strategies that could be more targeted and efficacious against cardiac fibrosis. Computational models of cardiomyocyte signaling have successfully been used to predict which signaling nodes are most important for cardiomyocyte hypertrophy in vitro[105,106] or how phenomena such as compartmentalization affect hypertrophy[107,108]. Markov models are also useful for determining the effect of ion channel mutations on electrical conduction[109].…”
Section: Future Directionsmentioning
confidence: 99%
“…Computational models can help identify the mechanisms by which these drugs suppress fibrosis and can identify therapeutic strategies that could be more targeted and efficacious against cardiac fibrosis. Computational models of cardiomyocyte signaling have successfully been used to predict which signaling nodes are most important for cardiomyocyte hypertrophy in vitro[105,106] or how phenomena such as compartmentalization affect hypertrophy[107,108]. Markov models are also useful for determining the effect of ion channel mutations on electrical conduction[109].…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, the authors confirmed that CT1 increases the length-width ratios of cells, in contrast to the pattern seen with phenylephrine, which they use as a pathological stimulus. In fact, cardiomyocyte elongation is seen in pathological hypertrophy and notable physiological growth pathways (e.g., neuregulin-1 and CITED4) inhibit elongation [6]. Moreover, phenylephrine itself likely also activates physiological growth pathways given the role of α-adrenergic signaling in postnatal cardiac growth [7].…”
mentioning
confidence: 99%
“…Exercise training downregulated Cebpb and upregulated Cited4, an observation which is consistent with previous findings showing necessary involvement of these transcriptional mediators in regulating physiologic growth. 45,46,[217][218][219] Moreover, the expression of Nfatc2, the deletion of which ameliorates pathological hypertrophy and heart failure but does not prevent physiological hypertrophy, 231 was markedly lower in hearts from exercise-adapted mice (Fig. 11F).…”
Section: Resultsmentioning
confidence: 97%
“…Expression of a dominantnegative form of PFK2 (Glyco Lo ) in the heart decreased glycolytic rate and was sufficient to modulate the Cebpb/Cited4 transcriptional program that regulates physiologic cardiac growth. 45,46,219 Mice in which myocardial glycolytic rate is constitutively high also showed slight hypertrophy, but these hearts did not engage the physiologic growth gene program. The corollary of these findings is that exercise-induced changes in phosphofructokinase activity are necessary to activate transcriptional programs dictating cardiac growth and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation